Penerapan Model Pembelajaran Modeling The Way Berbantuan Multimedia untuk Meningkatkan Keterampilan Menulis Paragraf pada Siswa Kelas III SDN Sumbermulyo 1 - Kolifah, Kolifah (Jurnal Simki Pedagogia, 2022)
The purpose of classroom action research is to improve students' skills in writing paragraphs with the multimedia-assisted the way modeling learning model for third grade students of SDN Sumbermulyo 1 Jogoroto Jombang. The type of research conducted is classroom action research through multimedia-assisted the way learning model based on three cycles. Each cycle consists of one meeting, namely planning, implementation, observation, and reflection. The research subjects were third grade students of SDN Sumbermulyo 1. Data collection techniques were test and non-test techniques. Data analysis through quantitative techniques. The results showed that the results of paragraph writing skills experienced a significant increase, it can be seen in the first cycle the class average achievement of the first cycle learning outcomes reached 65.83 with 64.29% classical completeness. This result increased in the second cycle with the average result of writing skills to 78.54 with 92.86% classical completeness. The conclusion of this research is that through multimedia-assisted the way modeling learning model can improve student activity and paragraph writing skills. Suggestions in the study are teachers can apply the multimedia-assisted the way modeling learning model, it is hoped that students will add insight to various learning sources and knowledge about various learning models in order to improve learning in schools.